Borrowing from '5-6' Lenders: Examining the Link Between Street Vendors' Profiles and Informal Borrowing Practices - Labitad, Jessa B (RIRAI Publisher, 2025)
This study examined the borrowing practices of street vendors in the Cogon public market, Cagayan de Oro, Philippines, with a specific focus on their reliance on the informal